ERP Project Lifecycle costs: A Review- - L’YARFI Hanane; MOTAKI Noureddine; DERRHI Mostafa (Journal of Digital information Management, 2023)
Today, many organizations acquire and implement enterprise resource planning (ERP) solutions to improve their operations performance and create value. However, they fail to achieve these objectives due to a lack of knowledge and a better estimating of all the costs related to an ERP system project. The purchasing costs of ERP systems are the most visible expense for many organizations that have adopted ERP systems, but the entire ERP lifecycle phase of implementation contains many hidden costs. As a result, institutions have long struggled with information system implementation cost overruns. This document presents the research on the various costs associated with the different stages of the life cycle of the REP project according to the literature on ERP lifecycle costs.

ERP Project Lifecycle costs: A Review- - L’YARFI Hanane; MOTAKI Noureddine; DERRHI Mostafa; LAHLOU Imane (Journal of Digital Information Management, 2023)
Today, many organizations acquire and implement enterprise resource planning (ERP) solutions to improve their operations performance and create value. However, they fail to achieve these objectives due to a lack of knowledge and a better estimating of all the costs related to an ERP system project. The purchasing costs of ERP systems are the most visible expense for many organizations that have adopted ERP systems, but the entire ERP lifecycle phase of implementation contains many hidden costs. As a result, institutions have long struggled with information system implementation cost overruns. This document presents the research on the various costs associated with the different stages of the life cycle of the REP project according to the literature on ERP lifecycle costs.

Knowledge-Intensive Decision Support System for Manufacturing Equipment Maintenance - Djamila Bouhalouan; Bakhta Nachet; Abdelkader Adla (Journal of Digital Information Management, 2020)
To ensure continuous production in industrial plants, the high valued manufacturing eqipments should be kept in good working conditions. This brings plants to search for means to control and reduce equipment failures. When faults emerge in plants, appropriate actions for fault diagnosis and reparation must be executed promptly and effectively to prevent large costs due to breakdowns. To provide reliable and effective maintenance support, the aid of advanced decision support technology utilizing previous repair experience is of crucial importance for the expert operators as it provides them valuable troubleshooting clues for new faults. Artificial intelligence (AI) technology, particularly, knowledge-based approach is promising for this domain. It captures efficiency of problem solving expertise from the domain experts; guides the expert operators in rapid fault detection and maintenance. This paper focuses on the design and development of a Knowledge-Intensive Decision Support System (KI-DSS) for Manufacturing Equipment Maintenance in industrial plants to support better maintenance decision and improve maintenance efficiency. With integration of case based Reasoning and ontology, the Ki-DSS not only carries out data matching retrieval, but also performs semantic associated data access which is important for intelligent knowledge retrieval in decision support system. A case is executed to illustrate the use of the proposed KI-DSS to show the feasibility of our approach and the benefit of the ontology support.

A New Approach Based Symbiotic Organism Search using Data Mining for Medical Decision- - Samia Nouredine; Abida Toumi; Baarir Zineeddine (Journal of Digital Information Management, 2020)
In the medical field the decision represents an extremely important asset because the risk must be zero. This is why decision approaches which are based on a predictive vision are a must solution. The decision is generally based on the exploitation of a large volume of medical data. The processing and analysis of mass data is only possible through an extraction of knowledge allowing the medical experts to make the best decision. Thus to meet this need, data mining has become the most promising approach. There are several techniques of datamining, and although they are quite developed the y still remain even less efficient notably the classical meta-heuristics. In this paper, we are exploiting a new meta-heuristic called symbiotic organisms search (SOS) that is based on a biological process. In this paper, we develop the formal model of the SOS based data mining process in the medical field with a comparative study with other metaheuristics to show its performance and credibility of treatment.

Corpus-Based Techniques for Sentiment Lexicon Generation: A Review- - Mohammad Darwich; Shahrul Azman Mohd Noah; Nazlia Omar; Nurul Aida Osman (Journal of Digital Information Management, 2019)
State-of-the-art sentiment analysis systems rely on a sentiment lexicon, which is the most essential feature that drives their performance. This resource is indispensable for, and greatly contributes to, sentiment analysis tasks. This is evident in the emergence of a large volume of research devoted to the development of automated sentiment lexicon generation algorithms. The task of tagging subjective words with a semantic orientation comprises two core approaches: dictionarybased and corpus-based. The former involves making use of an online dictionary to tag words, while the latter relies on co-occurrence statistics or syntactic patterns embedded in text corpora. The end result is a linguistic resource comprising a priori information about words, across the semantic dimension of sentiment. This paper provides a survey on the most prominent research works that utilize corpus-based techniques for sentiment lexicon generation. We also conduct a comparative analysis on the performance of state-of-the-art algorithms proposed for this task, and shed light on the current progress and challenges in this area.

Fault Prediction in Fuzzy Discrete Event Systems: A Diagnoser Approach- - Bilal Benmessahel; Farid Nouioua; Mohamed Touahria; Abderrahim Chariete (Journal of Digital Information Management, 2019)
In this workm we study the fault prediction in fuzzy discrete event systems. Fuzzy discrete event systems are proposed to deal with vagueness, impreciseness, and subjectivity in real-world problems. The verification is divided into two steps. In the first step, we give a method to construct a Diagnoser. And in the second step, based on the structure of diagnoser we give the necessary and sufficient conditions to verify the future occurrence of the fault. The newly proposed approach allows us to deal with the problem of fault prediction for both crisp DESs and FDESs. Finally, an example is provided to illustrate the efficiency of the proposed approach.

A Survey on Vehicular Ad-Hoc Networks Routing Protocols: Classification and Challenges - TASSOULT Nadia; MAD Mourad; MOUMEN Hamouma; KALLA Hamoudi (Journal of Digital Information Management, 2019)

A Survey on Vehicular Ad-Hoc Networks Routing Protocols: Classification and Challenges- - TASSOULT Nadia; AMAD Mourad; MOUMEN Hamouma; KALLA Hamoudi (Journal of Digital Information Management, 2019)
The Vehicle ad hoc Networks (VANET) are attracting more and more manufacturers and researchers’ attention. Many challenges must be addressed before VANETs can be successfully deployed. The most challenging issue in VANETs is designing of routing mechanisms and efficient medium access control protocols so that safety related and other application messages can be timely and reliably disseminated through VANETs. The aim of VANET routing protocols is establishing of an efficient route between network nodes that should adapt to the rapid changes in the network topology. However, routing protocols in VANET is a challenging issue, mainly due to the rapidly changing topology of vehicles and frequent fragmentation in the network. In this work, we review the most frequent routing protocols for VANETs and then we provide a taxonomy of these protocols based on the used relay selection technique. We compare and discuss these routing protocols according to different criteria. Moreover, we discuss several issues and prerequisite that should be considered when designing VANETs routing. Finally, we highlight the most important aspects and future directions that could be explored in the design of a new Geocast routing solution for vehicular routing algorithms as a contribution for further work.

Temporal Trends Analysis for Dengue Outbreak and Network Threats Severity Prediction Accuracy Improvement- - Nurfadhlina Mohd Sharef; Nor Azura Husin; Khairul Azhar Kasmiran; Mohd Izuan Ninggal (Journal of Digital Information Management, 2019)
Time series analysis is one of the major techniques in capturing trends and pattern of the occurrence for future forecasting. Existing but scarce works have developed temporal-based techniques which target to either predict movement (increase or decrease) or quantify the possibility of the predicted event to happen. Many of these techniques focus on the values of the time series attribute but there is no available work on dengue or intrusion logs that focus on temporal trend analysis-based on temporal relations mining. In this work the proposed technique utilize the temporal trends analysis of the observational attributes towards the pattern of the target’s attribute values. In this work, we propose a new temporal trends analysis approach that uses temporal relation mining in forecasting dengue outbreak and cyber intrusion. We leverage the temporal abstractions and temporal logic to define patterns with the goal to optimize prediction accuracy. From the experiment conducted, the results showed that the proposed approach has better prediction as compared to the baseline.

Temporal Trends Analysis for Dengue Outbreak and Network Threats Severity Prediction Accuracy Improvement- - Nurfadhlina Mohd Sharef; Nor Azura Husin; Khairul Azhar Kasmiran; Mohd Izuan Ninggal (Journal of Digital Information Management, 2019)

Applied Management Support for an Efficient WSN Infrastructure - Nilayam Kumar Kamila; Sunil Dhal; Bhagirathi Nayak (Journal of Networking Technology, 2018)
There are many management applications such as disaster management, air pollution management, weather management, traffic control management etc. which requires continuous attentions and prompt actions. Inclusion of theory of management support and timely decision to any un-managed system will improve the performance, usability and sustainability. Wireless Sensor Network is a self build infrastructure which deployed on the areas where there is no continuous power supply to the sensor nodes. There are many researches and approach has been proposed and protocols designed to address the network performance. We analyzed and identified the issue areas where management support and timely organized decisions improve the wireless sensor network performance. We categorized the system based on levels of management and presented our proposed protocols in all levels with process flow and performance comparisons through our simulation models.

A Comparative Analysis of the Efficiency of Video Reader Object for Frame Extraction in MATLAB - M Nachamai; Joy Paulose; Samuel Marandi (Journal of Multimedia Processing and Technologies, 2018)

Efficient Management of Community Question Answering Sites using Improved Spectral Clustering – - Abhishek Kumar Singh; Naresh Kumar Nagwani; Sudhakar Pandey (Journal of Digital Information Management, 2018)
Community Question-Answering(CQA) sites are the major platform where posts are generated by peers in the form of questions and answers for information seeking in online environments. In general, multiple posts are created by different users on a particular topic or subject. Large number of posts raises the difficulties in information management of these sites. A number of approaches are suggested in recent research work for efficient management of data for CQA sites. Many of the existing approaches have suggested use of clustering techniques for managing the CQA sites, but ignored the tagging data (user tags) of the posts. In this paper, an improved spectral clustering technique is derived based on similarity measures for text processing (SMTP) and utilized for clustering the posts considering the tagging data available on CQA sites. A specialized data structure, namely, folksonomy is developed for clustering using the relationship between tags, posts and users.

Efficient Management of Community Question Answering Sites using Improved Spectral Clustering - Abhishek Kumar Singh; Naresh Kumar Nagwani; Sudhakar Pandey (Journal of Digital Information Management, 2018)

Future Reference Sentence Extraction in Support of Future Event Prediction- - Yoko Nakajima; Michal Ptaszynski; Hirotoshi Honma; Fumito Masui (International Journal of Computational Linguistics Research, 2018)

Model Integration Approach from SysML to MATLAB/Simulink- - Bassim CHABIBI; Adil ANWAR; Mahmoud NASSAR (Journal of Digital Information Management, 2018)

Model Integration Approach from SysML to MATLAB/Simulink- - Bassim CHABIBI; Adil ANWAR; Mahmoud NASSAR (Journal of Digital Information Management, 2018)
In system engineering process, descriptive system models seem to be insufficient in order to perform a system verification which fulfils various stakeholders’ requirements. This aspect is well handled by simulation process through the use of several simulation techniques or algorithms. As a consequence, design process efficiency is considerably reduced by the fact that both system modeling and simulation tools are often used separately. This study introduces an integration process to unify the potential provided by systems modeling languages and simulation environments, through the definition of a Domain Specific Language, namely Simulation Modeling Language, that is built on the basis ofa deep study of common constructs, semantics and modeling methodologies of several simulation environments, in addition to the specification of a model transformation between this language and a simulation environment (MATLAB/SImulink) in order to illustrate both its importance et its efficiency in our integration approach. Through the specification of its syntaxes and semantics, the defined intermediate modeling language allows modeling systems by using common constructs and modeling methodologies of simulation process in order to ensure their modeling with simulation environments

Play-driven Design: Model for Engaging Person as in Content Sites - Angelo Públio; Sergio Nesteriuk (Journal of Information Organization, 2018)

Query Optimization on Distributed Health Database DBD by Minimizing Attribute Involvement - Slamet Sudaryanto N; Sudaryanto; Maryani S (Journal of Digital Information Management, 2018)

Text Classification for Arabic Words Using BPSO/REP-Tree - Hamza Naji; Wesam Ashour; Mohammed Al Hanjouri (International Journal of Computational Linguistics Research, 2018)

Text Classification for Arabic Words Using BPSO/REP-Tree - Hamza Naji; Wesam Ashour; Mohammed Al Hanjouri (International Journal of Computational Linguistics Research, 2018)

OCC-mix approach for concurrent mixture of fixed and mobile transactions - Al-Qerem, A.; Hamarsheh, A.; Nashwan, S. (Journal of Digital Information Management, 2017)

Application of K-means algorithm to web text mining based on average density optimization - Fan, G.-L.; Liu, Y.-W.; Tong, J.-Q.; Zhao, S.-H.; Nie, Z.-Q. (Journal of Digital Information Management, 2016)

An improved SMOTE algorithm based on genetic algorithm for imbalanced data classification - Gu, Q.; Wang, X.-M.; Wu, Z.; Ning, B.; Xin, C.-S. (Journal of Digital Information Management, 2016)

Mining Frequent patterns through microaggregation in differential privacy - Ni, Z.; Li, Q.M.; Liu, X.Q.; Li, T.; Hou, R. (Journal of Digital Information Management, 2015)

Application of finite volume method for solving two-dimensional Navier Stokes equations - Ni, J.; Wei, X. (Journal of Digital Information Management, 2013)
The finite volume method combines the advantage of the finite element method and the finite difference method, while overcoming their shortcomings. This paper describes the development of the finite volume method and the process of using finite volume method for fluid calculations. Finally, this paper introduces the process of using improved finite volume method for solving the flow equations of NS.
Keywords: Finite volume method; NS equations; Riemann

The integration of PCA, FLD and gabor two-dimensional wavelet transformation using facial expression feature extraction - Ni, J.; Li, Y. (Journal of Digital Information Management, 2013)
In order to improve the rate of facial expression recognition. The Gabor wavelet fusion PCA+FLD method is proposed as a new method this paper. Firstly, face image preprocessing, and then carries on the two-dimensional wavelet transform Gabor, first constructed five scale eight directional wavelet filter, through the PCA+FLD method for dimensionality reduction, and finally obtaining an optimum expression a projection subspace classifier in all the optimal subspace. The experiment proves, fusion PCA, FLD and Gabor wavelet transform two-dimensional facial expression feature extraction for classifier design, facial expression recognition rate is high. The experiment proves that the new method of Gabor wavelet fusion PCA+FLD is perfect.
Keywords: Facial expression recognition; PCA+FLD; Two dimensional gabor wavelet

Tuning of PID controller for air conditioning unit based on adaptive genetic algorithm - Zhou, Y.-T.; Nie, J.-B.; Han, N.; Li, D.; Chen, C. (Journal of Digital Information Management, 2013)
PID control is widely used in air conditioning system. The algorithm is simple but has a long response time, and the adjustment is not flexible. In this paper, we propose a method of optimizing PID controller parameters based on adaptive genetic algorithm. Specifically, the fitness function with penalty terms is added to the classical genetic algorithm and adaptive crossover and mutation factor genes to make the PID parameters converge to global optimum quickly. In addition, the method can prevent overshoot and improve stability effectively. Simulation results indicate that our method achieved a 83% reduction in regulation time of response of an airconditioning unit compared with the original PID system . The method can be used for online tuning of PID parameters as well.
Keywords: Adaptive genetic; Air-conditioning unit; Control system; Penalty factor; PID parameter optimizatio

Developing and deploying cloud services based on abstraction approach - Nguyen, B.M.; Tran, V.; Hluchy, L. (Journal of Digital Information Management, 2012)
With the advance of cloud computing, the trend of developing and deploying applications on cloud environment also has appeared recently. There are economic as well as technological reasons why an application should be developed and deployed on the cloud. Reducing costs and business agility are typical business factors for cloud-based applications. Cloud computing can provide significant cost savings because of the increased utilization resulting from the pooling of resources. In addition, this technology enables rapid delivery of IT services, which also improves business efficiency. On the operational side, manageability, performance, and scalability are the typical reasons why application developers consider cloud computing. However, cloud computing is still considerable complex to use. Not only the migration between clouds is difficult - but also the development and deployment of a new, complex service from the beginning could be quite a challenge using today's cloud computing. In this paper, novel high-level abstraction layers for cloud computing is presented. The abstraction layers will allow users to manage cloud resources form various clouds and simplify the process of developing and deploying services into those clouds. This approach will also solve absolutely the interoperability issue, thus improving the flexibility of cloud computing.
Keywords: Abstraction; Cloud computing; Cloud-based application; Interoperability; Object-oriented programming

Exploring lexicographic ontologies for hierarchically organizing the greek wikipedia articles - Niarou, M.; Stamou, S. (Journal of Digital Information Management, 2012)
To effectively manage the proliferating online content, it is imperative that we come up with efficient data structuring and organization methods. Based on the findings of previous research [6] [7] that the most flexible and useful way to organize the online content is via the use of taxonomies and/or ontologies, we carried out the present study, which aims at structuring the content of the Greek Wikipedia via the use of the Greek WordNet. In particular, our study objective is to design a model that can automatically organize the Greek Wikipedia categories into a thematic taxonomy and based on the derived organization, to implicitly assign hierarchical structure to the encyclopedia articles that have been classified to the respective categories. To this end, we relied on the data encoded in Greek WordNet out of which we harvested the hierarchical relations that hold between the terms used to verbalize the Wikipedia categories. The effectiveness of our model is verified by the findings of several experimental evaluations conducted, which demonstrate that semantic networks are powerful resources for hierarchically organizing large volumes of dynamic data.
Cited By (since 1996):1Export Date: 10 July 2014
Keywords: Hierarchical organization; Wikipedia articles; WordNet

Middleware model for adapting dynamic requirements - Suganthi, S.; Nadarajan, R. (Journal of Digital Information Management, 2012)
Making a distributed system adaptable to the dynamic variations in the user requirements is a big challenge in software industries. It is identified that the solution for the adaptability of such dynamic variations can be achieved through reflective middleware. In this paper an efficient solution is proposed by combining aspect oriented approach with reflective middleware. The significant feature of the proposed aspect oriented reflective middleware model is capturing the dynamic variations in the functionalities of the system as aspects. The three major components defined in this model to implement dynamic adaptability are Aspect Generator, Aspect Weaver and Remote Method Invoker. Aspect Generator component is used to define dynamic requirements as aspects. Aspect Weaver provides service to weave the dynamic requirements with the application components associated with that requirement. Remote Method Invoker is the meta layer component, which provides the platform for the Aspect Weaver to execute its service. The metric to measure the efficiency of the system adaptability has also been proposed here. The adaptability approach implemented through this model has been evaluated and proved as an efficient solution using this metric. This model has also been evaluated at an architectural level using formal analysis to prove that the dynamic requirements can be incorporated without affecting the existing functionalities of the system.
Keywords: Adaptability Metric; Aspect-Oriented Approach; Aspect-Oriented Reflective Middleware; Dynamic Adaptation; Dynamic Requirements; Reflective Middleware

Password based anonymous authentication with private information retrieval - Nakamura, T.; Inenaga, S.; Ikeda, D.; Baba, K.; Yasuura, H. (Journal of Digital Information Management, 2011)
This paper focuses on authentication with three types of entities: a user who sends an authentication request, a service provider who receives and verifies the request, and a database who supplies the service provider with information for verifying the request. This paper presents novel authentication protocols that satisfy the following important properties: (1) secure against replay attacks and (2) the database cannot identify which user is authenticating. First, we show a protocol which satisfies Properties (2). Second, we show a protocol which satisfies Properties (1) and (2). A key idea of our authentication protocols is to use private information retrieval (PIR) [Chor et al. J. ACM, 1998].
Keywords: Anonymity; Authentication; Privacy protection; Private information retrieval

Role of segment progressive filter in dynamic data mining - Naqvi, M.; Hussain, K.; Asghar, S.; Fong, S. (Journal of Digital Information Management, 2011)
Association rule mining perhaps the most widely described technique among the minding paradigms. The temporal association rule mining in the association rule mining tries to find relations among items in datasets. The temporal association mining has strength in detecting the dynamic nature of databases. Unfortunately the current mining methods ignore the consideration of database content updates. In the current research we have introduced the Incremental Standing method for Segment Progressive Filter (ISPF). The proposed technique can support the database update and mine updated datasets. We prove that the proposed algorithm is an optimal way of mining. We have applied the scan reduction technique to generate all candidate k-item sets to form 2-candidate item sets directly. We also bring good experimentation to validate and document clearly the algorithm with good examples.
Keywords: Mining algorithms; Segment Progressive Filter; Temporal association rules

Task-oriented dialogue agent architecture - Nestorovič, T. (Journal of Digital Information Management, 2011)
This paper focuses our agent-based approach to dialogue management equipped with a deliberation mechanism further extensible with additional features. The aim of this study has been to create a manager which can exhibit complex behaviour from two points of view - the development and runtime ones. To support the first case, the domain developer needs to provide a set of plans which tell the agent how to cope with particular tasks. Then during the runtime, the agent processes these plans to manage the dialogu e in accordance with an optimization criterion specifed. This paper summarizes our effort and gives an overview about our architecture.
Keywords: Agent-based dialogue management; Artifcial intelligence; Dialogue systems; System adaptability

Extraction of features for diagnosing pneumoconiosis from chest radiographs obtained with a CCD scanner - Nakamura, M.; Abe, K.; Minami, M. (Journal of Digital Information Management, 2010)
This paper presents a computer-aided diagnosis for pneumoconiosis radiographs obtained with a common CCD scanner. Since the existing diagnosis systems for pneumo coniosis extract abnormalities of pneumoconiosis from im ages obtained with a special scanner which can appropri-ately-apply-for-chest- radiographs,-it-is-difficult-toapply the systems to images obtained with a CCD scanner due to un clear shadow and the systems are not practical for medical doctors due to high costs. In the unclear images, the ab normal levels of pneumoconiosis could depend on density distribution in each of intercostal and rib areas. Therefore, the proposed method measures the abnormalities by extract ing characteristics of the distribution in the areas. Besides, using the-abnormalities,-the-proposed-method-classifies-the-imagesinto the three categories of pneumoconiosis. Exper imental results-of-the-classifications-for- 51-right-lung-im-ages-including 6 pneumoconiosis images have shown that the proposed abnormalities are well extracted according to the standards of pneumoconiosis categories.
Cited By (since 1996):2Export Date: 10 July 2014
Keywords: Chest radiographs; Computer-aided diagnosis; Medical image processing; Pneumoconiosis

Web Architectural-Inducing Model (WA-IM) for Information Architecture in cultural context: An empirical investigation - Mohd Isa, W.A.R.W.; Md Noor, N.L.; Mehad, S. (Journal of Digital Information Management, 2010)
Website Information Architecture (IA) is primarily treated as a new discipline that is concerned with design principles and architecture of information in digital landscape. Proliferation of revolutionary models for interdisciplinary applications of IA, however lack theoretical perspectives, empirical evidence and cultural context. Here, we proposed a new model called Web Architectural-Inducing Model (WA-IM). The model was developed based from existing literature and available architectural proposition from prior work. We tested the model suggesting that website IA being conceptualized as multidimensional constructs by exploring the applicability of WA-IM to web localization process from a socio-cognitive cultural perspective. The research methodology involves a web-based survey on Muslim online user as the cultural case study where 427 usable international responses were accumulated. The construct validation of the multifactor structure of website IA was assessed via confirmatory factor analysis (CFA) by using structural equation modeling. AMOS 7.0 was used to evaluate the five factor hypothesis goodness fit model. The result revealed that website IA is indeed a multidimensional construct composed of five factors: content-information, content-trust, navigation-traits, navigation-wayfindings and context. We conclude our study by providing empirical evidence for WA-IM in a form of goodness-fit-structure as part of the localization process towards the creation of cultural information structure.
Keywords: Human computer interaction; Information architecture; Information structure; Website information architecture

Cache Pre-fetching and Replacement strategies for location dependent data in mobile environments - Mary Magdalene Jane, F.; Ilayaraja, N.; Nadarajan, R. (Journal of Digital Information Management, 2009)
In this paper, new strategies for prefetching and cache replacement are proposed. The proposed pre-fetching algorithm considers the geographical and semantic adjacency between queried items. The strategy is to pre-fetch the most probable secondary service as a by-product of the execution of a query to a primary service. Association rule mining is used for determining the secondary item that should be pre-fetched. The latter part of the paper deals with a cache replacement algorithm PAID+ (Probability Area Inverse Distance +) which takes into account the access probability and distance between the mobile client and the service item which suits a pre-fetching environment. The experimental evaluations using synthetic datasets show the cache pre-fetch and replacement policy PAID+ are effective in improving the system performance in terms of the cache hit ratio of mobile clients.
Keywords: Cache replacement; Location dependent data; Prefetching algorithm

Distributed Web 2.0 crawling for ontology evolution - Juffinger, A.; Neidhart, T.; Granitzer, M.; Kern, R.; Weichselbraun, A.; Wohlgenannt, G.; Scharl, A. (Journal of Digital Information Management, 2009)
The World Wide Web as a social network reflects changes of interest in certain domains. It has been shown that free online content available through blogs, wikis, news media and online forums is a valuable source of information to identify trends in certain domains. Utilizing this data, one can construct ontologies that describe this information and provide a semantically correct overview of a domain. Tracked over time this also enables a user to identify trends and hypes. The decentralised structure of the Internet, the huge amount of data and upcoming Web2.0 technologies pose several challenges to a crawling system for ontology learning, evolution and trend analysis. This paper presents a distributed crawling system with browser integration for Web2.0. The proposed crawler is a high performance Web data retrieval system aimed to gather browser-equivalent textual Web content and prepare it for ontology learning.
Keywords: Distributed crawling; Executed crawling; Ontology evolution; Ontology learning; Web 2.0 crawling

Implementation of a chain ontology based approach in the health care sector - Omran, E.; Bokma, A.; Al-Maati, S.A.; Nelson, D. (Journal of Digital Information Management, 2009)
Preserving privacy and managing data access have become crucial requirements for enterprises who deal with personal data. Hippocratic databases (Agrawal et al, 2002) and the Chain method (Fedaghi, 2007) have been proposed to support this through candid database design that includes responsibility for the privacy of data as a founding tenet. We identify, study, and implement several privacy-preserving features that extend the previous work on Limiting Disclosure in the Chain method. These features include the support of Ontology in the database design, Ontology design in OWL and applying a hybrid approach of Chains and Ontologies to a Health-care use case. The proposed approach tries to bring the Chain method one step closer to fitting real-world scenarios. We present the design and implementation guidelines of each of the proposed features. The evaluation of the design shows how the ontology has simplified the complicated work of designing the traditional Hippocratic and chain methods for real databases.
Keywords: Chain ontology; Health care; Personal databases; Personal ontology; Privacy management

Smart electronic visitor information management system with biometric verification - Noraziah, A.; Noorhuzaimi, M.N.; Junaida, S. (Journal of Digital Information Management, 2009)
Smart Electronic Visitor Information System (SEVIMS) is an application to replace traditional visitor registration and information management activities. SEVIMS able to record visitor information during visitor registration by using visitor's Malaysia Government Multipurpose Card (MyKad). An implementation of mobile smart card reader with biometric verification has increase the high level of security and access control. With additional features, the identity of visitor can be verify based on matching of his/her thumbprint with the thumbprint image stored in MyKad. The benefits of sophisticated SEVIMS are enhancing the level of security enforced in premises, providing an organized view of visitor records and reducing the time spent on managing visitor information.
Cited By (since 1996):2Export Date: 10 July 2014
Keywords: Biometric; Fingerprint; MyKad; SEVIMS; Smart card

An improved biometric template protection method based on non-uniform quantization - Han, Q.; Wang, Z.; Niu, X. (Journal of Digital Information Management, 2008)
In recent literature, the issue of biometric template protection was raised. Some schemes were proposed to solve the contradiction between the fuzzy biometric information and accurate cryptography functions to achieve the protection of biometric template via cryptography method. In this paper, a novel methodology to achieve the security of the biometric templates in biometric systems is proposed. An adaptive non-uniform quantization (ANUQ) algorithm is introduced to eliminate the contradiction between the fuzziness of the biometric information and the sensitive of the Hash function. The ANUQ algorithm maps different biometric feature vectors from the same individual to a unique quantized feature vector. Then the quantized feature vector can be saved and identified by its hash and the biometric system can be free from the risk of the leakage of users' privacy information. Based on the ANUQ algorithm, two biometric template protection scheme are designed to meet different applications. Scheme-I involved a single quantizing template while scheme-II use a quantizing template array. The comparison of the two schemes are raised. Further, the testing of these schemes are carried out on an iris recognition algorithm. The results show the feasibility of the ANUQ-based schemes.
Cited By (since 1996):5Export Date: 10 July 2014
Keywords: Biometrics template; Non-uniform quantization; Privacy security; Quantizing template

Query planning in the PORDaS P2P database system - Nørvåg, K.; Eide, E.; Standal, O.H. (Journal of Digital Information Management, 2008)
Computational science is a rapidly growing multidisciplinary field that has a need for scalable, distributed, and efficient data management. In our research, we see the peer-to-peer (P2P) paradigm a possible solution to some of the problems in distributed data management. P2P has already proved to be suitable in contexts like file sharing, distributed computations, and distributed search. In our research we are aiming at using P2P to solve some problems in the domain of distributed databases. In this paper we 1) present PORDaS, a distributed DBMS based on P2P techniques, 2) describe query processing and query planning in PORDaS, and 3) present results from an experimental evaluation of different query planning variants.
Keywords: Data grid; Distributed databases; Peer-to-peer; Query processing

Restricted continuous KNN queries on road networks with caching enhancement - Safar, M.; Ebrahimi, D.; Jane, M.M.F.; Nadarajan, R. (Journal of Digital Information Management, 2008)
Using a Global Positioning System (GPS) in the car navigation system enables the driver to perform a wide range of queries, from locating the car position, to finding a route from a source to a destination, or dynamically selecting the best route in real time. With spatial network databases (SNDB), objects are restricted to move on pre-defined paths (e.g., roads) that are specified by an underlying network. In our previous work, we proposed a novel approach, termed Progressive incremental Network Expansion (PINE), to efficiently Support several spatial queries. In this work, we utilize our developed PINE system to efficiently support Restricted Continuous K Nearest Neighbors (RCKNNs) queries. RCKNN continously finds the K nearest objects to a query point an a given path that are within a specified distance bound. Our solution addresses a new type of query that is plausible to many applications where the answer to the query not only depends an the distances of the nearest neighbors, but also on the user ar application needs. By distinguishing between two types of split points, we reduce the number of computations required to retreive the RCKNNs of moving object. We futher define a caching model to expedite RCKNN query response time.
Cited By (since 1996):2Export Date: 10 July 2014
Keywords: Navigation system; Network databases; Spatial databases

Robust video watermarking based on dual-plane correlation for immunity to rotation, scale, translation, and random distortion - Atomori, Y.; Echizen, I.; Dainaka, M.; Nakayama, S.; Yoshiura, H. (Journal of Digital Information Management, 2008)
A robust video watermarking method is described that can embed watermarks immune to not only rotation, scaling, and translation but also to random geometric distortion and any of their combinations. It can detect watermarks without any search for canceling the effect of random distortion. Rotation, scale, and translation are canceled by searching for the angle, size, and origin of the original picture. The search for the angle and size is combinatorial but is independent of the search for the origin. That is, the angle and size of the target picture can be restored without restoring the picture's origin. Furthermore, the search for the origin is divided into horizontal and vertical searches that can be carried out independently. The number of searches is thus drastically reduced, making the processing speed high enough for practical application. Experimental evaluation using actual video samples demonstrated that the proposed method can embed watermarks immune to all four types of transformations.
Cited By (since 1996):5Export Date: 10 July 2014
Keywords: Random distortion; RST; Survivability; Video watermarking

Topic maps management in spatial-temporal multimedia blogs - Rajbhandari, S.; Andres, F.; Naito, M.; Wuwongse, V. (Journal of Digital Information Management, 2008)
Web-based blogging has entered the mainstream of society as an easy way to publish information, and it is exponentially increasing the data volume and its related complexity. Spatial-temporal information (Where and When contexts) contained inside multimedia postings needs to be better semantically handled by search engines or by end-users as current web blogs still lack semantic support. The semantic web community has promoted Topic Maps as a technology that reduces the lack of semantics regarding optimization of information creation, exchange, navigation, merging, and dissemination. This paper introduces a new layer that combines blogging standards (e.g. RSS and Atom) with the Topic Maps data model for semantic-augmented and interoperable information exchange support. In addition, the paper includes examples from the Isfahan Islamic Architecture DataBase (IIADB) project, the pilot user of the topic maps layer bridging the semantic gap of multimedia postings in a historical and architectural context.
Keywords: Multimedia blogs; Topic maps; Web based blogs

Adaptive turbo coded OFDM - Haider, S.A.; Noori, K. (Journal of Digital Information Management, 2007)
In this paper the system throughput of an OFDM system is enhanced by adding turbo coding and adaptive modulation (AD). Simulation is done over a time varying Raleigh fading channel. Each OFDM block is individually modulated according to channel state information acquired during the previous burst. The system automatically switches from higher to lower order modulation in order to maintain a constant bit error rate. Turbo codes are added for forward error correction, in addition to adaptive modulation. The end goal is to increase the system throughput while maintaining a bit error rate (BER) of 10-2.
Cited By (since 1996):1Export Date: 10 July 2014
Keywords: Adaptive modulation; OFDM; Turbo coding

The Infocious Web search engine: Improving Web searching through linguistic analysis - Ntoulas, A.; Chao, G.; Cho, J. (Journal of Digital Information Management, 2007)
In this paper we present the Infocious Web search engine [23], which currently indexes more than 2 billion pages collected from the Web. The main goal of Infocious is to enhance the way that people find relevant information on the Web by resolving ambiguities present in natural language text. Towards this goal, Infocious performs linguistic analysis to the content of the Web pages prior to indexing and exploits the output of this analysis when ranking and presenting the results to the users. Our hope is that this additional step of linguistic processing provides Infocious with two main advantages. First, Infocious tries to gain a deeper understanding of the content of Web pages and to match the users' queries with the indexed documents better, improving the relevancy of the returned results. Second, based on its linguistic processing, Infocious tries to organize and present the results to the users in a structured and more intuitive way. In this paper we present the linguistic processing technologies that we investigated and/or incorporated into the Infocious search engine, and we discuss the main challenges in applying these technologies to Web documents. We also present the various components in the architecture of Infocious, and how each one of these components benefits from the added linguistic processing. Finally, we present preliminary results from our experimental study that evaluates the effectiveness of the described linguistic analysis.
Keywords: Infocious search engine; Linguistic processing; Web pages; Web search engines

A layered MIMO OFDM system with channel equalization - Noori, K.; Haider, S.A. (Journal of Digital Information Management, 2007)
This paper proposes a simple and efficient method for layered MIMO-OFDM system with channel equalization. Temporal variations in the channel are due to Doppler spread, a sign of relative motion between transmitter and receiver. Results are simulated in both Rayleigh channel and additive white Gaussian noise (AWGN) channel. Decision feedback equalizer (DFE) with recursive least square (RLS) algonthm is used for channel equalization. Different type of Layered structure is applied to MIMO-OFDM system and their performance is evaluated. Different modulations schemes are used with same number of transmit and receive antennas. Simulation results are shown for both vertical and horizontal coded layered structure MIMO-OFDM systems with different modulation schemes and different number of transmit antennas.
Cited By (since 1996):1Export Date: 10 July 2014
Keywords: Graphsdecomposition algorithm; VDM; Vienna development method